Active deformation, kinematics and mechanics of Eastern Sicily : morphostructurale analysis and analogue modeling - (:unkn) unknown (My University, 2020)
In Central Mediterranean, Sicily is known for its intense volcanic activity (Mount Etna, Aeolian Islands) and its major historical earthquakes (Noto, 1693, M 7.4 ; Messina, 1908, M 7.1). These events reflect a particularly active geodynamic context, controlled by deformation mechanisms and interactions between deep tectonics and surface processes (erosion, sedimentation) that are still poorly understood.During the Mesozoic, the opening of the Neo-Tethys, between the future Europe and Africa plates, shaped the geometry of the surrounding continental margins, particularly in the North African domain. The Alpine Tethys, the western branch of this ancient ocean, closed during the Cenozoic through a system of fast subductions and collisions developing in a context of slow convergence between the Africa and Eurasia plates. The Calabro-Sicilian Arc, and more generally the Apennines-Maghreb system, result from the retreat of the Alpine Tethys, followed by the continental subduction of the African and Apulian margins under the AlKaPeCa continental blocks (Alboran, Kabylia, Peloritan and Calabria) with the African and Apulian margins. These micro-continental blocks, derived from the European margin, accompanied the slab rollback towards the South-East, localizing at their front the accretion of the Alpine Tethys sedimentary cover and opening in their wakes a series of back-arc basins (Algerian-Provençal and Tyrrhenian basins). From North to South, Eastern Sicily is divided into four tectono-stratigraphic domains : 1) the Peloritain-Calabria block, detached from the Corso-Sardinian micro-continent since the opening of the Tyrrhenian 15 Ma ago, 2) the pelagic sediments of the Alpine Tethys, remnants of the oceanic accretionary prism, 3) the Meso-Cenozoic cover of the African margin accreted since the Middle Miocene, and 4) the present day foreland represented by a thick carbonate platform (Hyblean Plateau), separated from the Ionian domain by the Malta Escarpment
Keywords: African Research